Addressing Pain in Neonatal Cancers: A Systematic Review - Anbazhagan, S; Priyadarshini, G. Nevetha; subramanian, v v; Parthasarathy, S (Journal of Neonatal Surgery, 2025)
Background: Neonatal cancers are a rarity, but this makes them all the more challenging, given the uniqueness of the physiological and developmental characteristics of neonates. Critical attention on effective pain management for this population is highly warranted, yet it often remains unaddressed. Objective: The aim of this systematic review is to summarize the existing literature on pain management strategies pertaining to neonatal cancers, investigate the quality of the current studies, highlight the knowledge gaps, and suggest orientations for future research. Methods: A comprehensive literature search was carried out from PubMed, Scopus, and the Cochrane Library, using keywords relating to neonatal cancer and management of pain. The target population incorporated peer-reviewed research articles, clinical guidelines, and observational studies published between 2000-2023. Data were extracted by the PICO framework while methodological quality was assessed by GRADE criteria. Results: The approaches of pain management revealed substantial heterogeneity without any consensus set on the best practice. Common standardized pain assessment tools included Neonatal Infant Pain Scale and Premature Infant Pain Profile, but their implementation varied from study to study. The pharmacological interventions (opioids and non-opioid analgesics) were supplemented with non-pharmacological therapies like skin-to-skin contact and sucrose analgesia. The barriers stated were lack of training among healthcare providers, misconceptions about neonates with respect to pain perception, and lastly, absence of clear guidelines. The non pharmacological therapies are more oriented towards addressing acute pain than chronic pain. Conclusions: While effective pain management for neonatal cancers is warranted, lots of factors confound the process. Future research should look at standardizing pain traits, designing training for healthcare providers, and developing guidelines on evidence-based practice to improve care quality. Attention to these issues would greatly serve treatment outcomes and quality of life for neonates undergoing treatment for cancer. Non-pharmacological therapies, such as cognitive-behavioral techniques, physical interventions, and relaxation methods, can effectively alleviate neonatal cancer pain, minimizing drug side effects and enhancing overall patient comfort and well-being.